The Motives for Issuing Central Bank Digital Currency and the Challenges of Introduction Thereof - Terták, Elemér; Kovács, Levente (Public Finance Quarterly, 2022)
Summary: The idea of a central bank digital currency arose ten years ago for the first time, but by now it has become one of the most frequently discussed topics in the field of finances. Currently, some 100 central banks are researching and investigating the concept of a central bank digital currency (CBDC) and its implementation options.1 Over half of these central banks have reached the development stage, and some are already conducting on-site experiments. However, the intense interest and the efforts made have not yet led to an increasing number of implementations, since so far only the Bahamas (Sand Dollar), the Member Countries of the Eastern Caribbean Currency Union (DCash) and Nigeria (eNaira) have introduced a CBDC. The other countries are currently still in one of the preparatory stages. The article briefly reviews the history of money digitalisation, and describes the various motives for issuing a CBDC, as well as the variety of challenges faced in the process of introducing a CBDC. It also presents the preparations taken so far for the introduction of the digital Euro, as well as Sweden’s e-krona. Finally, it summarises the authors’ views on the strategy Hungary should follow regarding a CBDC.